Loss of IL13RA2 promotes metastatic tumor growth in triple-negative breast cancer via increased AKT and NF-κB signaling - Wendy E. Bindeman; Kevin C. Corn; Marjan Rafat; Barbara Fingleton (Clinical & Experimental Metastasis, 2025)
Triple-negative breast cancer is associated with poor patient prognosis and high rates of distant metastasis. These patients are at elevated risk of brain metastasis, which remains a major therapeutic challenge. IL13RA2, a high-affinity receptor for IL13, is highly expressed in primary brain cancers, many extracranial solid tumors, and in lung- and brain-seeking metastatic variant cell lines. However, the relationship between IL13RA2 and patient prognosis is variable, and the biological function of this receptor in cancer remains controversial. We sought to define the role of IL13RA2 in triple-negative breast cancer growth and metastasis, with an emphasis on breast-to-brain metastasis. We generated IL13RA2-CRISPR knockout derivatives of the human brain-seeking breast cancer cell line MDA231BrM2, as well as murine 4T1 cells, and evaluated changes in gene expression, proliferation, survival, and metastatic growth in vivo. Both IL13RA2-deficient models demonstrate enhanced cell survival in vitro, as well as augmented metastatic tumor growth and worsened animal survival in intracardiac models of brain metastasis. Concordantly, elevated IL13RA2 mRNA expression is positively correlated with overall survival in patients with basal-like breast cancer. Mechanistically, IL13RA2-deficient cells exhibit increased AKT and NF-κB signaling. These cells are sensitive to inhibition of either pathway, but especially AKT, which may represent a clinically useful vulnerability for patients with IL13RA2-low tumors. Our data suggest that inhibition of IL13RA2, though promising in other tumor contexts, may be deleterious in metastatic triple-negative breast cancer.

Glycosylation as a regulator of site-specific metastasis - Wendy E. Bindeman; Barbara Fingleton (Cancer and Metastasis Reviews, 2022)

Development of a novel murine model of lymphatic metastasis - Babak Banan; Jacob A. Beckstead; Lauren E. Dunavant; Yoojin Sohn; Jamie M. Adcock; Sachiyo Nomura; Naji Abumrad; James R. Goldenring; Barbara Fingleton (Clinical & Experimental Metastasis, 2020)

The importance of developing therapies targeting the biological spectrum of metastatic disease - Andries Zijlstra; Ariana Von Lersner; Dihua Yu; Lucia Borrello; Madeleine Oudin; Yibin Kang; Erik Sahai; Barbara Fingleton; Ulrike Stein; Thomas R. Cox; John T. Price; Yasumasa Kato; et al. (Clinical & Experimental Metastasis, 2019)

Non-canonical roles for metabolic enzymes and intermediates in malignant progression and metastasis - Demond Williams; Barbara Fingleton (Clinical & Experimental Metastasis, 2019)

Perspective on the interpretation of research and translation to clinical care with therapy-associated metastatic breast cancer progression as an example - Barbara Fingleton; Kelly Lange; Beth Caldwell; Katherine V. Bankaitis (Clinical & Experimental Metastasis, 2017)

Meeting report: Metastasis Research Society–Chinese Tumor Metastasis Society joint conference on metastasis - Katherine Bankaitis; Lucia Borriello; Thomas Cox; Conor Lynch; Andries Zijlstra; Barbara Fingleton; Miodrag Gužvić; Robin Anderson; Josh Neman (Clinical & Experimental Metastasis, 2017)

Targeting IL4/IL4R for the treatment of epithelial cancer metastasis - Katherine Venmar Bankaitis; Barbara Fingleton (Clinical & Experimental Metastasis, 2015)

Establishment and quantitative imaging of a 3D lung organotypic model of mammary tumor outgrowth - Michelle D. Martin; Barbara Fingleton; Conor C. Lynch; Sam Wells; J. Oliver McIntyre; David W. Piston; Lynn M. Matrisian (Clinical & Experimental Metastasis, 2008)

Use of bioluminescent imaging to investigate the role of nuclear factor-κΒ in experimental non-small cell lung cancer metastasis - Georgios T. Stathopoulos; Taylor P. Sherrill; Wei Han; Ruxana T. Sadikot; Vasiliy V. Polosukhin; Barbara Fingleton; Fiona E. Yull; Timothy S. Blackwell (Clinical & Experimental Metastasis, 2008)

An Orthotopic Model of Lung Cancer to Analyze Primary and Metastatic NSCLC Growth in Integrin α1-Null Mice - Xiwu Chen; Yan Su; Barbara Fingleton; Heath Acuff; Lynn M. Matrisian; Roy Zent; Ambra Pozzi (Clinical & Experimental Metastasis, 2005)